Bestandskundliche Untersuchungen an wirtschaftlich wichtigen Grundfischbeständen im Nordost-Atlantik - Schöne, Rüdiger (2004)
For many years the assessments of the commercially most important demersal fish stocks of cod, haddock, saithe, redfish and Greenland halibut have annually been carried out by the "Arctic Fisheries Working Group" of ICES. The most important results of the actual assessment are given in this report. It shows that the gadoid stocks of cod, haddock and saithe are in good and stable conditions and that the stocks are harvested within safe biological limits. The stocks of redfish and Greenland halibut are still at a low level and outside safe biological limits. Greenland halibut shows a slightly positive trend in spawning stock biomass, several year-classes and recruitment.